2017
DOI: 10.1021/acscatal.7b01151
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Cobalt-Catalyzed C(sp2)–H Borylation of Five-Membered Heteroarenes with Pinacolborane

Abstract: Studies into the mechanism of cobalt-catalyzed C(sp2)−H borylation of five-membered heteroarenes with pinacolborane (HBPin) as the boron source established the catalyst resting state as the trans-cobalt(III) dihydride boryl, (iPrPNP)Co(H)2(BPin) (iPrPNP = 2,6-(iPr2PCH2)2(C5H3N)), at both low and high substrate conversions. The overall first-order rate law and observation of a normal deuterium kinetic isotope effect on the borylation of benzofuran versus benzofuran-2-d1 support H2 reductive elimination from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…However, outside of aryl halide coupling reactions, there have in recent years appeared examples of homogeneous catalysis by pincer-supported Co complexes where two-electron OA/RE steps are either well understood or strongly suggested. [32][33][34][35][36][37][38][39][40][41][42] In 2018, we reported on the reactivity of (POCOP) Co(Ph)(SPh). 43 In contrast to (PNP)Rh(Ph)(SPh) 18 or (POCOP) Rh(Ph)(SPh), 19 it did not undergo C-S RE but instead a RE of the phenyl with the pincer aryl (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, outside of aryl halide coupling reactions, there have in recent years appeared examples of homogeneous catalysis by pincer-supported Co complexes where two-electron OA/RE steps are either well understood or strongly suggested. [32][33][34][35][36][37][38][39][40][41][42] In 2018, we reported on the reactivity of (POCOP) Co(Ph)(SPh). 43 In contrast to (PNP)Rh(Ph)(SPh) 18 or (POCOP) Rh(Ph)(SPh), 19 it did not undergo C-S RE but instead a RE of the phenyl with the pincer aryl (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…While this manuscript was completed, Chirik et al reported on an adventitious borylation step in a PNP Co-complex. 10 The unique feature of our organo-boron compounds is the wide range of accessible products gained through C-C bond formation.…”
Section: Ligand Synthesismentioning
confidence: 99%
“…A sequence involving oxidative addition of a B–H or B–B followed by H–H or H–B reductive elimination, possibly involving phosphine dissociation, [11] generates the intermediate responsible for activation of the C( sp 2 )–H bond of the substrate (Schemes 2a and 2b). [5a,8,9] …”
Section: Introductionmentioning
confidence: 99%
“…Modification of the 4‐position of the pincer preceded borylation of the substrate . A cobalt(I)‐boryl compound was also identified as the C( sp 2 )−H activating species during the borylation of 5‐membered heteroarenes with HBPin but competing borylation of the cobalt pincer complex was not observed . With these heteroarenes and boron source, the catalyst resting state is the cobalt(III) complex, trans ‐( iPr PNP)Co(H) 2 BPin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation